Experimental study of the γp→π0ηp reaction with the A2 setup at the Mainz Microtron; Physical Review C; Vol. 97, iss. 5 - Sokhoyan V.; Prakhov S.; Fiks (Fix) A. I. Alexander Ivanovich; Abt S. (2018, 2018)
Title screen